2016
DOI: 10.1590/0100-67622016000400011
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Arboreal Leguminous Plants and Maize Yield in Agroforestry Systems

Abstract: -Forest plantation costs can be reduced by the income from annual crops that are intercropped with trees. An experiment was carried out over two years to assess the viability of agroforestry systems including sabiá (Mimosa caesalpiniifolia), gliricidia (Gliricidia sepium) and maize (cultivar AG 1051). In 2010, the legumes were grown both as monocrops and intercropped (taungya system) with maize in randomized blocks with five replications. Three rows of maize were planted between two rows of each legume (at a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Em consequência do modelo de produção integrado os componentes interagem em sinergismo e também, às vezes, antagonismo. O sombreamento gerado pela árvore pode prejudicar o desenvolvimento da lavoura como foi observado por Mendes et al 2013 Do ponto de vista econômico, Oliveira et al (2016) indicam que a lavoura contribuí para redução dos custos da implantação da floresta com a venda de espigas verdes e grãos, embora o componente florestal influa sobre as características produtivas do milho.…”
Section: Lavouraunclassified
“…Em consequência do modelo de produção integrado os componentes interagem em sinergismo e também, às vezes, antagonismo. O sombreamento gerado pela árvore pode prejudicar o desenvolvimento da lavoura como foi observado por Mendes et al 2013 Do ponto de vista econômico, Oliveira et al (2016) indicam que a lavoura contribuí para redução dos custos da implantação da floresta com a venda de espigas verdes e grãos, embora o componente florestal influa sobre as características produtivas do milho.…”
Section: Lavouraunclassified
“…Area ( In general, the literature suggests that agroforestry systems, independent of the species used, offer a wide range of potential impacts, including socioeconomic ones. Oliveira et al (2016) showed that an agroforestry system with maize and two legume species, Mimosa caesalpiniifolia, which were tolerant to semiarid conditions, and Gliricidia sepium, a Brazilian caatinga species, provided greater productivity of green maize and consequently higher net income and a reduction in the cost of reforestation.…”
Section: Municipalitymentioning
confidence: 99%
“…Changes in the Caatinga biome have already resulted in it reaching approximately 50% of its original vegetation, making it the third most degraded biome in Brazil, behind only the Atlantic forest and Cerrado [1,2]. Although cattle raising is one of the main activities in the region, it is among the main sources of interference in the Caatinga due to the extensive practice of grazing, non-adjustment of grazing pressure, and grazing at inappropriate times, which are driven by the difficulty of monitoring and estimating yield parameters of forage plants [3][4][5].…”
Section: Introductionmentioning
confidence: 99%